2015
DOI: 10.1186/s13673-015-0043-0
|View full text |Cite
|
Sign up to set email alerts
|

Time evolution of face recognition in accessible scenarios

Abstract: Up to now, biometric recognition has shown significant advantages as to be considered a reliable solution for security systems in mobile environments. Nevertheless, due to the short lifetime of biometrics in mobile devices, a handful of concerns regarding usability and accessibility need to be covered in order to meet users’ requirements. This work is focused on analysing the usability and accessibility of a face recognition system used by visually impaired people, focusing on the time spent in the process, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 28 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…Further experiments have analysed the convenience of using specific modalities for elderly [ 2 ], [ 10 ] and for people with visual impairments [ 11 ]–[ 13 ], concluding that biometric recognition could ease common tasks such as banking transactions or mobile authentication. In studies of biometrics with elderly users, outcomes suggest that users have initial anxieties due to distrust and fear of unknown technologies.…”
Section: State Of the Artmentioning
confidence: 99%
“…Further experiments have analysed the convenience of using specific modalities for elderly [ 2 ], [ 10 ] and for people with visual impairments [ 11 ]–[ 13 ], concluding that biometric recognition could ease common tasks such as banking transactions or mobile authentication. In studies of biometrics with elderly users, outcomes suggest that users have initial anxieties due to distrust and fear of unknown technologies.…”
Section: State Of the Artmentioning
confidence: 99%
“…As noted previously, research has also shown that the physiology of a user can affect the performance of a biometric system, including age [21] and accessibility [34]. Another important factor when discussing how users affect system performance is to examine users' acceptance and satisfaction of biometric systems as this, in turn, will not only drive the overall performance but will indicate the willingness to use such a system.…”
Section: Factor #Iv: Usersmentioning
confidence: 99%
“…Image plays an important role in numerous human activities such as law enforcement [12, 13], agriculture and forestry management [14, 15], earth science [16] and so forth. One of the uses of images is in face recognition and identification [17, 18]. …”
Section: Introductionmentioning
confidence: 99%